[Rezension von: Rose, Colin, 1986-, A renaissance of violence] - Muurling, Sanne (Crime, histoire & sociétés, 2021)
Early modern northern Italy presents an interesting conundrum in the debates about the causes of the long-term historical decline of lethal violence. Explanations for the centuries-long decline in homicide usually broadly rely on Elias’ theory of the civilizing process, suggesting that self-control rose as individuals internalised social controls promoted by the expansion of the state and the extension of the market economy. But northern Italy until the eighteenth century had not only develop...